Literature Review : Pemanfaatan Computer-Assisted Audit Techniques (CAATs) dalam Evaluasi Pengendalian Internal untuk Deteksi Kecurangan pada Siklus Pengeluaran - Dyah Rizki Arinengsih (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the role of Computer-Assisted Audit Techniques (CAATs) in evaluating internal control within accounting information systems (AIS) to detect fraud in the expenditure cycle. The research employs a literature review method by analyzing five relevant studies selected based on publication criteria within the last ten years and a focus on technology-based auditing, internal control, and fraud. The findings indicate that CAATs, through features such as test data and parallel simulation, are effective in identifying system weaknesses, detecting transaction anomalies, and strengthening controls in the expenditure cycle. Fraud in this cycle is commonly caused by weak authorization, incomplete documentation, and expenditures conducted without proper procedures. CAATs address these challenges through data-driven and automated audit approaches. In conclusion, CAATs represent a strategic solution for enhancing monitoring accuracy, preventing fraud, and supporting organizational transparency and accountability in the digital era.